The Implementation of An Integrated Information System for Vocational Education and Training: A Case Study of Indonesia - Rizqi Aji Surya Putra; Eko Marpanaji (Journal of Information Technology and Education (JITED), 2025)
The integration of an information system in vocational education and training (VET) is essential for improving workforce readiness and aligning education with labor market needs. This study explores the implementation of a nationwide vocational information system in Indonesia, based on Presidential Regulation No. 68 of 2022. Using a case study approach, the research examines policies, system development, and stakeholder involvement. The findings show that the system improves access to labor market data but faces challenges in integration, user adoption, and data compatibility. Key success factors include strong government support, industry collaboration, and the use of digital platforms for real-time job market insights. The study highlights the need for ongoing investment in digital infrastructure and collaboration between the government, education institutions, and industries. This research provides practical insights into the benefits and challenges of implementing an integrated vocational information system, with recommendations for improving its effectiveness.